Investigating innovative drainage management tools to reduce nutrient runoff in surface drains in Rangitikei sand country : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management, Massey University, Palmerston North, New Zealand - Cramp, Lucy (Massey University, 2019)
Approximately 2.5 million hectares of land in NZ is currently artificially drained. However, while being beneficial to the system, drains have been identified as providing a direct conduit for nutrient loss from agricultural lands to receiving waters, potentially leading to detrimental effects instream. The aim of this thesis was to investigate targeted drainage management tools that can reduce nutrient runoff in surface drains in an intensive sand country dairy farm in the Rangitikei district. Drainage patterns and water quality was characterised, and then macrophyte management, real time swapping; and the potential for harvesting and recycling drainage water was investigated. Surface water samples were collected and analysed weekly for a period of nine months from June 2018 to February 2019 to characterise the drainage patterns and drainage water quality. Monitoring for real time swapping and macrophyte management trials took place between December 2017 and February 2018. Spatial and temporal trends were then analysed, and the potential of harvesting and reuse of drainage water for irrigation was assessed. Nitrate-N was identified as a problem pollutant in this study, with concentrations varying from 0.06 g/m³ to 5.96 g/m³ over the course of a year. OVERSEER estimated an average nitrogen loss of 25.9 g/m³ from the root zone to drainage waters. However, an overall average of only 3.3 g/m³ was observed. During the swapping trial period (January – March), average Nitrate-N levels in both the groundwater and drain waters were consistently low (<0.20 g/m³), meaning that swapping had no effect. Under the macrophyte trial, there was suggestion towards nutrient uptake with increasing macrophyte cover, but ongoing research is needed to find a definitive relationship. Under the Harvesting and Recycling exercise, it was found that nitrate-N attenuation costs are influenced by the concentration of N in the drainage water, and if there is an existing irrigation system. It is more cost effective ($0.34 per Kg N attenuated/yr) if the drainage nitrate-N concentration is higher and is recycled over previously un-irrigated land. These research findings will help to develop appropriate in-field or edge-of field management practices, and inform nutrient management plans for intensified land use to maintain or enhance water quality in the region. Potential progression could be to further study options to control and treat surface drainage water by controlled drainage, combined with wetlands, in order to reduce nutrient loads from intensive farms in the region.
The following Figures were removed for copyright reasons: Fig 2.1 (=Follett, 2008 Fig 2), 2.2 (=Leinweber et al., 2002, Fig 2.5) & 2.5 (=Hua et al., 2016 Fig 1).
Keywords: 410504 Surface water quality processes and contaminated sediment assessment